Determination of Geochemical Bio-Signatures in Mars-Like Basaltic Environments - Olsson-Francis, Karen; Pearson, Victoria K.; Steer, Elisabeth D.; Schwenzer, Susanne P. (Frontiers in Microbiology, 2017)
Bio-signatures play a central role in determining whether life existed on early Mars. Using a terrestrial basalt as a compositional analog for the martian surface, we applied a combination of experimental microbiology and thermochemical modeling techniques to identify potential geochemical bio-signatures for life on early Mars. Laboratory experiments were used to determine the short-term effects of biota on the dissolution of terrestrial basalt, and the formation of secondary alteration minerals. The chemoorganoheterotrophic bacterium, Burkholderia sp. strain B_33, was grown in a minimal growth medium with and without terrestrial basalt as the sole nutrient source. No growth was detected in the absence of the basalt. In the presence of basalt, during exponential growth, the pH decreased rapidly from pH 7.0 to 3.6 and then gradually increased to a steady-state of equilibrium of between 6.8 and 7.1. Microbial growth coincided with an increase in key elements in the growth medium (Si, K, Ca, Mg, and Fe). Experimental results were compared with theoretical thermochemical modeling to predict growth of secondary alteration minerals, which can be used as bio-signatures, over a geological timescale. We thermochemically modeled the dissolution of the basalt (in the absence of biota) in very dilute brine at 25°C, 1 bar; the pH was buffered by the mineral dissolution and precipitation reactions. Preliminary results suggested that at the water to rock ratio of 1 × 107, zeolite, hematite, chlorite, kaolinite, and apatite formed abiotically. The biotic weathering processes were modeled by varying the pH conditions within the model to adjust for biologic influence. The results suggested that, for a basaltic system, the microbially-mediated dissolution of basalt would result in “simpler” secondary alteration, consisting of Fe-hydroxide and kaolinite, under conditions where the abiotic system would also form chlorite. The results from this study demonstrate that, by using laboratory-based experiments and thermochemical modeling, it is possible to identify secondary alteration minerals that could potentially be used to distinguish between abiotic and biotic weathering processes on early Mars. This work will contribute to the interpretation of data from past, present, and future life detection missions to Mars.